Comparison of the results of researching the gelioroof in field and laboratory conditions - Шаповал, Степан Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
It is currently important to improve and create new solar panels that would allow us to reduce their cost and increase their efficiency. Therefore, we have suggested a connection between the solar collector and the building roof.The effectiveness of the gelioroof was tested in laboratory and field conditions. The energy efficiency of the roofing material has proved to be conducive to the solar collector productivity. We have suggested a matrix of planning a trifactoral experiment that accounts for interaction of the factors. The revealed empirical and graphical dependencies allow estimating the temperature of the heat carrier in the gelio panel depending on the incidence angle of the thermal flow and its intensity. The effectiveness of the gelioroof at different thermal flow incidence angles changed from 30° to 90°declines by 41 %, which is 20 % lower than in conventional solar collectors. We have also disclosed the results of the solar radiation intake by the gelioroof during the day within the gravitational system of solar heating. Day-time temperature changes in the heat carrier were measured in the battery tank, at the intake and the output of the gelioroof. The temperature of the heat carrier in the battery tank rose to 52° C, which confirms the effectiveness of the gelioroof.